1999
DOI: 10.1001/archinte.159.12.1301
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Mucormycosis

Abstract: Pulmonary mucormycosis is relatively uncommon but an important opportunistic fungal infection in immunocompromised persons. The literature on the subject is sparse. We describe a recent case and review the literature to delineate the clinical characteristics of this infection. We searched the MEDLINE database for articles published in the English-language literature since 1970 and carefully analyzed 87 cases. The main risk factors were diabetes mellitus, hematologic cancers, renal insufficiency, and organ tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
128
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(132 citation statements)
references
References 82 publications
(36 reference statements)
3
128
1
Order By: Relevance
“…Donahue et al (15) reported that there was susceptibility to endobronchial involvement in patients with diabetes. In a review conducted, it was reported that 85% of patients with endobronchial involvement had diabetes, as in our case (12). Hemoptysis is seen more in mucormycosis than bacterial pneumonias.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Donahue et al (15) reported that there was susceptibility to endobronchial involvement in patients with diabetes. In a review conducted, it was reported that 85% of patients with endobronchial involvement had diabetes, as in our case (12). Hemoptysis is seen more in mucormycosis than bacterial pneumonias.…”
Section: Discussionsupporting
confidence: 58%
“…The most common causes of delayed diagnosis are the simultaneous existence of viral or bacterial infections, not suspecting the disease, and difficulty of reproduction of fungi with conventional techniques (6). While the most frequent pre-mortem diagnosis is made by bronchoscopy, the most common technique is transbronchial biopsy (12). Since there was also endobronchial involvement in our case, a mucosa biopsy was conducted.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Bronchoscopy is the most common method used to obtain tissue; about 40% of patients with this condition will have visible endobronchial lesions which may be biopsied [4]. Histopathological examination of infected tissue will reveal broad nonseptate hyphae with right angle branching that is more sensitive than culture (sensitivity of 93 vs. 49%) [4]. As mucorales may be a contaminant, the clinical significance of isolating the organism from sputum and bronchoalveolar lavage is problematic [5].…”
Section: Discussionmentioning
confidence: 99%
“…The overall outcome is poor, with overall survival about 44% [4]. When diagnosed early, there may be a higher potential for cure.…”
Section: Discussionmentioning
confidence: 99%